Thermoregulatory and cardiovascular responses to creatine, glycerol and alpha lipoic acid in trained cyclists - Polyviou, T. P.; Pitsiladis, Y. P.; Lee, W.; Pantazis, T.; Hambly, C.; Speakman, J. R.; Malkova, D. (Journal of the International Society of Sports Nutrition, 2012)
It has been shown that supplementation with creatine (Cr) and glycerol (Gly), when combined with glucose (Glu) necessary for the enhancement of Cr uptake by skeletal muscle, induces significant improvements in thermoregulatory and cardiovascular responses during exercise in the heat. Purpose To determine whether Cr/Gly-induced thermoregulatory and cardiovascular responses are maintained when the majority (~75%) of the Glu in the Cr/Gly supplement is replaced with the insulintropic agent alpha lipoic acid (Ala). Methods 22 healthy endurance trained cyclists were randomly assigned to receive either 20 g/day (4 x 5 g/day) of Cr, 2 g .kg-1 BM per day (4 x 0.5 g .kg-1 BM per day) of Gly and 150 g/day (4 x 37.5 g/day) of Glu or 20 g/day (4 x 5 g/day) of Cr monohydrate, 2 g .kg-1 BM per day (4 x 0.5 g .kg-1 BM per day) of Gly (100 g/day (4 x 25 g/day) of Glu and 1000 mg/day (4 x 250 mg/day) of Ala for 7 days for 7 days. Exercise trials were conducted pre- and postsupplementation and involved 40 min of constant-load cycling exercise at 70% O2 max by a self-paced 16.1 km time trial at 30degreesC and 70% relative humidity. Results Median and range values of TBW increased significantly by 2.1 (1.3-3.3) L and 1.8 (0.2-4.6) L in Cr/Gly/Glu and Cr/Gly/Glu/Ala groups respectively (P = 0.03) and of BM not significantly by 1.8 (0.2-3.0) kg and 1.2 (0.5-2.1) kg in Cr/Gly/Glu and in Cr/Gly/Glu/Ala, respectively (P = 0.75). During constant load exercise, heart rate (HR) and core temperature (Tcore) were significantly lower post-supplementation: HR was reduced on average by 3.3 +/- 2.1 beats/min and by 4.8 +/- 3.3 beats/min (mean +/- SD) and Tcore by 0.2 +/- 0.1 (mean +/- SD) in the Cr/Gly/Glu and Cr/Gly/Glu/Ala, respectively The reduction in HR and Tcore was not significantly different between the supplementation groups. Conclusions In comparison to the established hyper hydrating Cr/Gly/Glu supplement, supplement containing Cr/Gly/Ala and decreased amount of Glu provides equal improvements in thermoregulatory and cardiovascular responses during exercise in the heat.